Microbia, Chemical Characteristics and Nutritional Value of Mango Probiotics Drink by Biocapsules Lactobacillus paracasei ssp. paracasei Ml.3 - Mutia, Elida; Agustina, Agustina; Fadhina, M.; Mega, Amelia Putri; Elviati, Elviati (Eximia, 2022)
This study aimed to investigate microbia amount, chemical properties and nutritional value of mango probiotics drink by biocapsules Lb. paracasei ssp. paracasei Ml.3. The production of biocapsules Lb. paracasei ssp. paracasei Ml.3 by extrusion carregenan-skim (2:1) of 12 bio-capsule. The result indicated that the exponential phase of the bio-capsule Lb. paracasei ssp. paracasei Ml3 at 17 hours of incubation required 2.09/hours of generation time and 8.12 generation number to reach 10.81 log CFU/ mL. The chemical characteristics indicated that the moisture content was 82.57%, ash content 0.12%, protein content 1.35%, fat content 0.2%, organic acid content 0.5%, vitamin C content 9.73% and crude fiber content 0.04%. Additionaly, this product contains 1.7x108 CFU/ mL Lb. paracasei ssp. paracasei Ml 3. According to the analysis of nutritional value (diet 2000 kkal) considerable high nutritional value and could be developed for functional food. This nutritional value showed protein were 0.949 kkal (0.47%), fat 1,71 kkal (0.43%), carbohydrate 74.373 kkal (5.31%) and total energy 77.032 kkal.